Impact of Emerging Agribusiness Establishments on Potato Marketing in Punjab - Grover, D. K.; Singh, J. M.; Singh, Jasdev; Kumar, Sanjay (Indian Journal of Marketing, 2014)
To revitalize agriculture in Punjab, crop diversification towards fruits and vegetables is being considered as one of the most promising alternatives. The major constraints inhibiting such diversification efforts have been the inadequate marketing opportunities for such crops owing to their perishable nature. Thus, there is a need to evolve innovative marketing institutions that link farmers with the markets for speedy and remunerative disposal. One such agribusiness enterprise - PepsiCo - has recently emerged in the state. The marketing experience of potato growers with this agribusiness establishment in Jalandhar district during 2009-10 has been studied. The study reveals that the share of the farmers in the retailer’s price under the traditional marketing system for potatoes was 42.29%, while the marketing costs as a percentage of the retailer’s price were 25.08%, and the marketing margins were 32.63%. The net price received by the farmers while selling the produce to PepsiCo was about 48% higher. The sample potato growers dealing with the newly emerged agribusiness establishment realized a higher benefit-cost ratio for potato cultivation with minimum post harvest losses. To reap the advantage of the emerging agribusiness environment in terms of enhanced farm income, potato growers need to be more product quality conscious as these institutions only buy selected quality produce of specific size, shape, and colour. The requisite training/campaigns can go a long way in augmenting agribusiness potential to enhance farm income through crop diversification in the state.